2021
DOI: 10.21203/rs.3.rs-558422/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptions, beliefs, and needs of Japanese people with knee osteoarthritis during conservative care: A qualitative study

Abstract: Background Patients’ perceptions and beliefs of disease could be influenced by their lifestyle and culture. Although it is important to understand their perceptions and beliefs toward disease to prevent and manage osteoarthritis (OA) through conservative care, this topic has not been investigated in Japanese people with knee OA. Therefore, this qualitative study aims to clarify how Japanese patients with knee OA experience and perceive their symptoms and disabilities, and how they face them during conservative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…The results of a qualitative studyonMalaysian older adults with KOA about the information required to enable them for self-managementrevealed that the patients' knowledge about KOA varied between individuals with many expressing that they needed more information about KOA ( 20 ). Also, another study showed that Japanese patients with KOA desired evidence-based information and to connect with other people in the same situation to solve problems related to their condition ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of a qualitative studyonMalaysian older adults with KOA about the information required to enable them for self-managementrevealed that the patients' knowledge about KOA varied between individuals with many expressing that they needed more information about KOA ( 20 ). Also, another study showed that Japanese patients with KOA desired evidence-based information and to connect with other people in the same situation to solve problems related to their condition ( 21 ).…”
Section: Discussionmentioning
confidence: 99%